The rational emotive behavioural approach to therapeutic change - Dryden, Windy (Sage therapeutic change series., 2004)
Change' is at the heart of Counselling and Psychotherapy. Clients enter into the therapeutic process in the hope that something in themselves or their situation will be different by the end. Counsellors and Psychotherapists therefore need to understand the nature of change and how best to facilitate it.